An Investigation on the Electrical Conductivity of Metal Matrix Composite Reinforcement Different Ceramic Particles - Aydın, Sezgin; Karip, Erdoğan; Muratoğlu, Mehtap (My University, 2015)
In this study, electrical conductivity was investigated for metal matrix composites produced by powder metallurgy techniques using different matrix like Al, Al-Bronze and copper. SiC, Al2O3 and graphite were used as a reinforcement. 5, 10 and 15 weight % these reinforcement were added to the matrix. The specimens were mixed for 30 and were pressed using 350 Mpa pressure, and sintered using different sintering temperature according to the used matrix materials. Using LCR test machine electrical resistances were calculated. It was observed that with increasing weight percentage of reinforcement electrical conductivity increased and the highest conductivity was obtained for graphite reinforced metal matrix composites. And also it was resulted that the effect of the reinforcement ratio was less effective on the condictivity of the composites having high condictivity matrix material
Keywords: Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kompozitler